Typhoid fever in children in Africa. - Mweu, E; English, M (2008)
Estimates for the year 2000 suggested that there were approximately 21.5 million infections and 200,000 deaths from typhoid fever globally each year, making the disease one of the most serious infectious disease threats to public health on a global scale. However, these estimates were based on little data, especially from Africa. Global prominence and high-profile outbreaks have created the perception in Kenya that typhoid is a common cause of febrile illness. The Widal test is used widely in diagnosis. We have reviewed recent literature, taking the perspective of a healthcare provider, to collate information on the prevalence of typhoid in children particularly, and to explore the role of clinical diagnosis and diagnosis based on a crude, but common, interpretation of the Widal test. Data suggest that typhoid in children in rural Africa is uncommon, perhaps 100 times or 250 times less common than invasive disease because of Haemophilus influenzae or Streptococcus pneumoniae, respectively. Frequent use of the Widal test may result in many hundreds of over-treatment episodes for every true case treated and may perpetuate the perception that typhoid is common. Countries such as Kenya need better bacterial disease surveillance systems allied to better information for healthcare providers to promote appropriate decision-making on prevention and treatment strategies.